Composite core-and-skirt collagen hydrogels with differential degradation for corneal therapeutic applications. (March 2016) - Rafat, Mehrdad; Xeroudaki, Maria; Koulikovska, Marina; Sherrell, Peter; Groth, Fredrik; Fagerholm, Per; Lagali, Neil
Abstract: Scarcity of donor tissue to treat corneal blindness and the need to deliver stem cells or pharmacologic agents to ensure corneal graft survival are major challenges. Here, new composite collagen-based hydrogels are developed as implants to restore corneal transparency while serving as a possible reservoir for cells and drugs. The composite hydrogels have a centrally transparent core and embedded peripheral skirt of adjustable transparency and degradability, with the skirt exhibiting faster degradation in vitro . Both core and skirt supported human epithelial cell populations in vitro and the skirt merged homogeneously with the core material to smoothly distribute a mechanical load in vitro . After in vivo transplantation in rabbit corneas over three months, composites maintained overall corneal shape and integrity, while skirt degradation could be tracked in vivo and non-invasively due to partial opacity. Skirt degradation was associated with partial collagen breakdown, thinning, and migration of host stromal cells and macrophages, while the central core maintained integrity and transparency as host cells migrated and nerves regenerated. Impact: This study indicates the feasibility of a collagen-based composite hydrogel to maintain corneal stability and transparency while providing a degradable peripheral reservoir for cell or substance release.